2019
DOI: 10.1039/c9dt01595g
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-induced tunable luminescence of luminomagnetic Dy and Ce co-doped ZnO nanoparticles

Abstract: Here, 1 mol% Dy,Ce co-doped ZnO nanoparticles were synthesized via combustion method and studied their structural, optical and magnetic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…A similar trend in lattice constant variation has been reported previously by other researchers. [ 26,29,30 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar trend in lattice constant variation has been reported previously by other researchers. [ 26,29,30 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 25 ] However, reports on the influence of (Ce, Dy) co‐doping on the structural and PL performance of the solution combustion synthesized ZnO nanoparticles are very limited, which led to the present investigation. Kalaiezhily et al [ 26 ] reported the tunable luminescence performance of combustion‐derived (Ce, Dy) co‐doped ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of lanthanide-doped ZnO materials, such as composites, films, nanoparticles etc., has already been reported in literature [7][8][9][11][12][13]. However, it's still unclear whether large number of lantanide ions can be dispersed in ZnO crystalline lattice or the ions can only segregate into crystalline lanthanide oxide due to large charge and radius of trivalent lanthanide ion.…”
Section: Introductionmentioning
confidence: 99%
“…A number of lanthanides doped ZnO materials, such as composites, films, nanoparticles etc., has already reported in literature [7][8][9][11][12][13]. However, it's still unclear whether large number of lantanide ions can be dispersed in ZnO crystalline lattice or the ions can only segregate into crystalline lanthanide oxide due to large charge and radius of trivalent lanthanide ion.…”
Section: Introductionmentioning
confidence: 99%